Strengthening of Agrarian Reform Implementation - Indriyani, Anggia; Agustina, Ika Surya (Jurnal Pertanahan, 2022)
ABSTRACT Creating an understanding between the Ministry of Agrarian Affairs and Spatial Planning/National Land Agency and related stakeholders to the community who will be the object of agrarian reform is the objectives of this research. The priorities among the SWOT components were carefully evaluated using a quantitative AHP-based SWOT analysis. SWOT aspects are used in this study, and a pairwise comparison technique and Focus Group Discussion (FGD). This study uses SWOT elements and Focus Group Discussion (FGD) pairwise comparison technique. The results of the comparison matrix show that the internal factor with the highest strength score is that agrarian reform can provide solutions to land problems, and the weakness is the absence or lack of assistance regarding agrarian reform activities. In contrast, the external factors with the highest opportunities and threats are the budget allocation for agrarian reform activities and the lack of public enthusiasm for implementing agrarian reform. So, that to overcome this, several strategies are carried out, namely conducting pre-surveys related to potential locations that are used as objects with approaches and counseling to the community to create public understanding of agrarian reform. In addition, carry out long-term planning and analyze potential data and problems faced during the program. Keywords: Agrarian Reform, Strategy, A’WOT (AHP and SWOT) ABSTRAK Memahami tujuan reforma agraria dalam mensukseskan kegiatan reforma agraria dan strategi pelaksanaan reforma agraria sehingga tercipta kesepahaman antara Kementerian Agraria dan Tata Ruang/Badan Pertanahan Nasional dan stakeholders terkait dengan masyarakat yang akan menjadi objek reforma agrarian adalah tujuan dari penelitian ini. Analisis SWOT berbasis AHP kuantitatif digunakan dalam penelitian ini untuk mengevaluasi secara sistematis prioritas di antara komponen-komponen SWOT. Penelitian ini menggunakan metode Teknik perbandingan berpasangan dari elemen SWOT dan Focus Group Discussion (FGD). Hasil matriks perbandingan menunjukkan bahwa pada faktor internal dengan skor kekuatan tertinggi adalah reforma agraria mampu memberikan solusi permasalahan pertanahan dan kelemahannya adalah belum adanya atau minimnya pendampingan mengenai kegiatan reforma agraria. Sedangkan pada faktor eksternal pada peluang dan ancaman yang paling tinggi adalah adanya alokasi anggaran untuk kegiatan reforma agraria dan kurangnya antusiasme masyarakat dalam melaksanakan reforma agrarian sehingga untuk mengatasinya dengan beberapa strategi yaitu melakukan pra survei terkait potensi lokasi yang dijadikan objek dengan pendekatan dan penyuluhan kepada masyarakat sehingga tercipta pemahaman masyarakat mengenai reforma agraria. Selain itu melaksanakan perencanaan jangka panjang dan menganalisa potensi data dan permasalahan yang akan dihadapi selama program berlangsung. Kata kunci: Reforma Agraria, Strategi, A'WOT (AHP dan SWOT)